Efforts to improve the physical quality of the elderly through the healthy living community movement (GERMAS) in Petiga Village - Adis Audiana Syafri; I Putu Ryan Dharma Putra; I Wayan Eka Mahendra (Universitas Muhammadiyah Magelang, 2021)
The death rate due to Covid-19 has continued to increase since it was first announced in early March 2020. This community service is carried out with the Healthy Living Community Movement (Germas) approach, one of which is physical activity. The activities were carried out using an educative and persuasive method for 4 months, starting from August to November 2021. This community service includes three types of activities, namely training and yoga assistance for elderly cadres, training in making herbal drinks (loloh) and establishing a tracking path for the elderly in Petiga Village. From a series of programs, the people of Petiga Village gave a positive response. These activities are able to provide benefits in accordance with the health problems of the elderly.